2010
DOI: 10.1007/s11739-010-0469-3
|View full text |Cite
|
Sign up to set email alerts
|

Time intervals and myocardial performance index by tissue Doppler imaging

Abstract: The application of tissue Doppler imaging (TDI) has shown remarkable growth in clinical practice during the past few years, especially, in risk stratification of patients with coronary heart disease or heart failure (systolic and diastolic). Myocardial performance index (MPI) is a Doppler echocardiographic parameter defined as the sum of the isovolemic contraction and relaxation times divided by the ejection time. It is considered as a reliable parameter to assess global left ventricular function. Cardiac time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 38 publications
(37 reference statements)
0
23
0
Order By: Relevance
“…27 Recent clinical studies also revealed that levosimendan does not cause any deterioration in diastolic function. 30 MPI decreases with increasing myocardial performance. The usefulness of MPI in the evaluation of systolic and diastolic function is well-known.…”
Section: Discussionmentioning
confidence: 91%
“…27 Recent clinical studies also revealed that levosimendan does not cause any deterioration in diastolic function. 30 MPI decreases with increasing myocardial performance. The usefulness of MPI in the evaluation of systolic and diastolic function is well-known.…”
Section: Discussionmentioning
confidence: 91%
“…Consequently, the accuracy of the results may be compromised by heart rate fluctuations. Tissue Doppler echocardiography enables us to simultaneously measure both the diastolic and systolic intervals from the myocardium [6]. …”
Section: Tdi Parametersmentioning
confidence: 99%
“…In the search for better selection criteria for CRT, it has been shown that patients with LV dyssynchrony have a higher likelihood of a positive response to CRT [6]. …”
Section: Tdi Parametersmentioning
confidence: 99%
“…TDI can be used to measure systolic time (St) and ejection time (ET) intervals in a noninvasive, geometrically independent, easily applicable fashion [1, 2]. Few authors, however, have evaluated these intervals in CHF patients [3, 4].…”
Section: Introductionmentioning
confidence: 99%